Genetic divergence in cauliflower (Brassica oleracea var botrytis subvar cauliflora) - SHARMA, K C; VERMA, S (The Indian Journal of Agricultural Sciences, 2014)
An experiment conducted during the winter season of 1998-99 and 1999-2000 to study variability and divergence in 9 diverse genotypes of cauliflower (Brassica oileracea L. var botrytis L. subvar cauliflora DC.). Significant differences were observed due to genotypes. The genotypic variances were of higher magnitude than that of the environmental variances for all the traits. The 9 eaulifower genotypes could be grouped into 3 diverse clusters. Majority orthe genotypes constituted cluster I. Leaves/plant contributed most towards divergence. Inter-cluster distance was the maximum between clusters II and III. The crosses may be attempted between the genotypes belonging to clusters II ('PSB 1, 'K I' and RSK II') and III ('Whiterock' and 'Grandessa') for getting desirable segregates for developing genetically superior variety (s) of cauliflower.